Tinjauan Yuridis Pasal 15 Undang-undang Pers terhadap Fungsi dan Kewenangan Dewan Pers dalam Mencegah Berita Bohong - Ernis Hutabarat; Ampuan Situmeang; Junimart Girsang (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2023)
This study aims to determine and analyze the function of the Press Council according to Article 15 of Law No. 40 of 1999 concerning the Press in its roles and actions in preventing hoax news. This research is a normative juridical analysis, by which the secondary data is in the form of the 1945 Constitution of the Republic of Indonesia Article 28 (F) and Article 15 of Law Number 40 of 1999 concerning the Press in particular. It is analyzed with a progressive legal theory from Satjipto Raharjo. The results of this study indicate that the Press Council, which has the status of an independent state institution, failed to maximize its role, especially its authority, in dealing with hoax news. The Press Law only has a simple function, like mediating press disputes. Due to its power, the Press Council has no authority to impose sanctions on violations committed by press companies. Moreover, the challenges faced no longer come from external sources but from the internal press itself, where currently, press companies often behave arbitrarily because the owners of press companies have used their media as a means of politics for the benefit of certain parties.